Landscape ecology in the Anthropocene: an overview for integrating agroecosystems and biodiversity conservation - Santos, Juliana Silveira dos [UNESP] (2021)
Recent studies have characterized the influence of agroecosystems on biodiversity. However, a set of components associated with the management of these areas is still neglected in landscape-level studies, especially in areas of recent agricultural intensification. The resources and conditions provided by agroecosystems to different species are highly variable in space and time, and failing to account for this variation may lead to misleading conclusions about the biodiversity status in these environments. In this perspective, we provide a conceptual overview to highlight why and which landscape components still need to be better explored to provide an adequate assessment of the agroecosystem effects on biodiversity. We used a Brazilian heterogeneous intensive-farming landscape as an example to outline the components that we believe are important for understanding biodiversity patterns in such landscapes. An in-depth description of agroecosystems can help us create better landscape-level management strategies and to design more effective green-way policies.